The Relationship Between Food-Based Pro-inflammatory Diet and Sarcopenia: Findings From a Cross-Sectional Study in Iranian Elderly People - Bagheri, Amir; Hashemi, Rezvan; Soltani, Sanaz; Heshmat, Ramin; Dorosty Motlagh, Ahmadreza; Larijani, Bagher; Esmaillzadeh, Ahmad (Frontiers in Medicine, 2021)
Background: Sarcopenia has rarely been linked to Food-based Inflammatory Potential of the Diet (FIPD) in earlier studies. This study was performed to examine the association of FIPD and sarcopenia and its components. Method: In the cross-sectional research, dietary intakes of 300 randomly-selected elderly adults aged 55 years or older were collected through a validated food frequency questionnaire. We constructed FIPD score based on average consumptions of 28 food items. According to The European Working Group on Sarcopenia definition, sarcopenia and its components such as muscle strength, muscle mass, and gait speed were defined. Result: No significant difference was found between the prevalence of sarcopenia (P = 0.05), low muscle mass (P = 0.27), low handgrip strength (P = 0.72), and lower gait speed (P = 0.14) across tertiles of FIPD score. Moreover, we did not find significant differences among means of handgrip strength (P = 0.65), muscle mass (P = 0.33), and walking speed (P = 0.89) across FIPD categories. However, binary logistic regression analysis indicated a significant positive relationship between FIPD score and odds of sarcopenia; such that subjects in the top vs. those in the bottom FIPD tertile had 155% greater chance of having sarcopenia (OR: 2.55; 95% CI: 1.17–5.55). After controlling for all confounding factors, this association strengthened (OR: 2.67; 95% CI: 1.18–6.01). Conclusion: We found that greater FIPD score, which means a more pro-inflammatory diet, was positively linked with sarcopenia.